Molecular Dynamics Simulations of Crystallite Interactions in Shock-compressed Columnar Polycrystals - Heighway, Patrick (Cranfield University, 2018)
Poster presented at the 2018 Defence and Security Doctoral Symposium.The need for a fundamental understanding of the strength of materials that are deforming extremely rapidly under high stress has driven intense research efforts on both theoretical and experimental fronts. Recent advances in "ultrafast" x-ray imaging techniques have made it possible to track how a material evolves during the course of extreme deformation processes that might take place over the course of only a few nanoseconds: by carefully analysing the image formed by x-rays scattered from the sample, one can calculate how its constituent atoms are arranged and, with further analysis, infer how strong the material is. However, the form of the x-ray image depends not only on the strength of the material, but also on the manner in which the crystallites of which it is composed interact with each other during the deformation process. We have performed a study of the physics of crystallite interaction in a shock-compressed metal using multi-million atom simulations. Our study reveals that neighbouring crystallites in the wake of the shock can deform in a "cooperative" manner, in which one crystallite expands while the other contracts. We quantify the change in atomic arrangement effected by this cooperative deformation, and the amount of stress it relieves. We further find that cooperative deformation can actually replace ordinary deformation mechanisms at lower pressures, and activate new deformation mechanisms at higher pressures.
Keywords: 'Shock compression'; 'Plasticity'; 'Molecular dynamics'; 'DSDS18 poster'; 'DSDS18'; 'Molecular Physics'